2010
DOI: 10.5398/medpet.2010.33.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Identification of Pit1 Gene in Indonesian Buffaloes (Bubalus bubalis) and Holstein-Friesian Cows

Abstract: Pit-1 gene has been identifi ed as the pituitary specifi c transcription factor that regulates the expression of the growth hormone (GH) and prolactin (PRL) genes in the anterior pituitary. The use of polymorphic markers in breeding programmes could make selection more accurate and effi cient. A total of 320 Indonesian buff aloes from four populations and 45 FH cows from nine populations were genotyped for polymorphism of Pit1|Hinf1 gene by the polymerase chain reaction and restriction fragment length polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
2
8
0
2
Order By: Relevance
“…Our results regarding Pit‐1 gene was supported by the finding of Misrianti et al. () and Othman et al. ().…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results regarding Pit‐1 gene was supported by the finding of Misrianti et al. () and Othman et al. ().…”
Section: Discussionsupporting
confidence: 89%
“…Our results regarding Pit-1 gene was supported by the finding of Misrianti et al (2010) and Othman et al (2011). They reported that all studied animals exhibited monomorphic pattern in Pit1Hinf1 locus in Indonesian and Egyptian buffaloes; thus, the association between Pit-1 gene and productive and reproductive traits could not be achieved due to the monomorphism.…”
Section: Discussionsupporting
confidence: 83%
“…Besides, the study of this gene was also intensively conducted in native cattle breeds in some countries, including Iranian cattle (Javanmard et al, 2005), Southern Anatolian red cattle (Oztabak et al, 2008), Hanwoo cattle (Han et al, 2010;Seong et al, 2011), Turkey cattle (Ozdemir, 2012), Qinchuan cattle (Zhang et al, 2009) and Piemontese cattle (Ribeca et al, 2014). Even more, Pit-1 gene was also identified in non-cattle species, including chicken (Nie et al, 2008), sheep (Bastos et al, 2006) and buffalo (Javanmard et al, 2005;Misrianti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that one SNP was in the exon 6 of bPit-1 gene at position g.1256G>A based on GenBank: Y15995 (Javanmard et al, 2005;Misrianti et al, 2010;Aytekin and Boztepe, 2013;Nahavandi et al, 2010;Chauhan et al, 2015;Bayram et al, 2017). Moreover, SNP of g.1256G>A can be detected by HinfI restriction enzyme through PCR-RFLP method (Dybus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%